The Genesis of the Theory of Taxation in the Western Scientific Tradition (Economic journal of Lesya Ukrainka Volyn National University, 2017)
The historical retrospective of the divergence of scientific theories of the taxation in the western scientific tradition and their influence on the formation of modern approaches to the construction of an efficient tax system are examined. It was found that the theoretical achievements of the coryphaeus’s of Western of economic science are the basis for understanding of the origins and mechanisms of taxation  the complex area of social reality in which many causal interaction between ideals and reality, theory and practice, economics and politics are intertwined. The research made it possible to substantiate the evolutionary way of understanding of the social nature of the tax by scientists of the West from the radical negation of taxes as an equal revenue of the state treasury, through the philosophical substantiation of this category and ideologization of practice of taxation, to the democratic tax forms of ensuring of social reproduction, as an inalienable attribute of a democratic state of law, defining conditions of civilized development of the society.
Keywords: theory, taxes, taxation, fiscal policy, budget.